Our experience in the use of prp therapy for the treatment of trauma and orthopedic patients - El Kandoussi, Sara; Maslennikov, S. O.; Kozhemyaka, M. O.; Масленніков, Сергій Олегович; Кожем'яка, Максим Олександрович (Запорізький державний медичний університет, 2021)
Introduction. Despite significant advances in the surgical treatment of patients with various injuries of the musculoskeletal system, we still try to resort to surgery last, when all attempts at a conservative solution are unsuccessful. In modern orthopaedics, regenerative medicine methods are relevant, including PRP therapy. Platelet-rich plasma (PRP) is a modern treatment strategy with worldwide recognition. PRP was introduced in the 1950s and is currently used in multiple fields of medicine. There is high concentration of platelet growth factors in small amounts of plasma. This works for offering an ''ideal environment'' for tissue regeneration and is part of the so-called biological therapy.
Keywords: тези